2019
DOI: 10.1038/s41467-019-12730-4
|View full text |Cite
|
Sign up to set email alerts
|

Energy transformation cost for the Japanese mid-century strategy

Abstract: The costs of climate change mitigation policy are one of the main concerns in decarbonizing the economy. The macroeconomic and sectoral implications of policy interventions are typically estimated by economic models, which tend be higher than the additional energy system costs projected by energy system models. Here, we show the extent to which policy costs can be lower than those from conventional economic models by integrating an energy system and an economic model, applying Japan’s mid-century climate mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…This study employs scenarios from five energy-economic and integrated assessment models: AIM/Enduse-Japan (Oshiro and Masui 2015;Fujimori et al 2019;Kainuma et al 2003), AIM/Hub-Japan (Fujimori et al 2017a, b, c;Silva et al 2019), DNE21 (Hosoya and Fujii 2011;Fujii and Komiyama 2015), IEEJ_Japan 2017 (Matsuo et al 2013(Matsuo et al , 2020, and TIMES-Japan (Kato and Kurosawa 2019;Kurosawa and Hagiwara 2012;Loulou et al 2005;Sato 2005). Hereafter, each model is called AIM/Enduse, AIM/Hub, DNE21, IEEJ, and TIMES-Japan.…”
Section: Model Descriptionmentioning
confidence: 99%
“…This study employs scenarios from five energy-economic and integrated assessment models: AIM/Enduse-Japan (Oshiro and Masui 2015;Fujimori et al 2019;Kainuma et al 2003), AIM/Hub-Japan (Fujimori et al 2017a, b, c;Silva et al 2019), DNE21 (Hosoya and Fujii 2011;Fujii and Komiyama 2015), IEEJ_Japan 2017 (Matsuo et al 2013(Matsuo et al , 2020, and TIMES-Japan (Kato and Kurosawa 2019;Kurosawa and Hagiwara 2012;Loulou et al 2005;Sato 2005). Hereafter, each model is called AIM/Enduse, AIM/Hub, DNE21, IEEJ, and TIMES-Japan.…”
Section: Model Descriptionmentioning
confidence: 99%
“…We used the AIM (Asia-Pacific Integrated Model) modelling framework as a tool for scenario quantification, which allowed us to assess macroeconomic factors globally, including the energy system, land use, agriculture, GHG emissions and climate, and has been utilised in various global and national studies 45,46,47,48,49 . The core of the modelling framework is the computable general equilibrium (CGE) model AIM/Hub (formerly named AIM/CGE).…”
Section: Overviewmentioning
confidence: 99%
“…In the energy demand sectors, numerous mitigation options are included in the sectors of industry, buildings, and transportation, such as energy-efficient devices and fuel changes. The details of these parameter assumptions have been reported previously (Fujimori et al 2019). Introduction of CCS is considered in the power and industry sectors, while CCS-ready and conversion to CCS-equipped plant after operation are not taken into account in the model.…”
Section: Sectormentioning
confidence: 99%
“…In this regard, several studies have assessed the energy and economic implications of Japan's near-to mid-term emission pathways using energy system models and integrated assessment models (IAMs), that integrate relevant disciplines such as energy, economy, agriculture, and land use into single modeling framework (Fujimori et al 2019;Kato and Kurosawa 2019;Oshiro et al 2019;Silva Herran et al 2019;. Generally, these national scenario analyses have suggested that attainment of both the NDC and MCS targets without strengthening the near-term target would require rapid emission reductions between 2030 and 2050, which would involve non-linear energy system transformation during this period (Oshiro et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation